Mathematics
JJBoone
6

X+2y=7 3x-2y=-3 solving systems by substitution

+0
(1) Answers
Jenny7

Move 2y to the right hand side of the equation by subtracting 2y from both sides. x=−2y+7  3x−2y=−3 Replace all occurrences of x with the solution found by solving the last equation for x. In this case, the value substituted is −2y+7. x=−2y+7  3(−2y+7)−2y=−3 Simplify each term. x=−2y+7  −6y+21−2y=−3 Add −6y and −2y to get −8y. x=−2y+7  −8y+21=−3 Move 21 to the right hand side of the equation. x=−2y+7  −8y=−21−3 Subtract 3 from −21 to get −24. x=−2y+7  −8y=−24 Divide each term in the equation by −8. x=−2y+7  y=3 Replace all occurrences of y with the solution found by solving the last equation for y. In this case, the value substituted is 3. x=−2(3)+7  y=3 Multiply −2 by 3 to get −6. x=−6+7  y=3 Add −6 and 7 to get 1. x=1  y=3 (1,3)

Add answer